Regioselective Synthesis of a Family of β‐Lactams Bearing a Triazole Moiety as Potential Apoptosis Inhibitors. Issue 5 (2nd August 2016) - Garrido, Maria; Corredor, Miriam; Orzáez, Mar; Alfonso, Ignacio; Messeguer, Angel
Abstract: Apoptosis is a biological process important to several human diseases; it is strongly regulated through protein–protein interactions and complex formation. We previously reported the synthesis of apoptosis inhibitors bearing an exocyclic triazole amide isoster by using an Ugi four‐component coupling reaction (Ugi‐4CC), followed by a base‐promoted intramolecular cyclization. Depending on the substitution patterns and the reaction conditions, this cyclization forms the six‐ or four‐membered ring. Two compounds bearing the β‐lactam scaffold turned out to be the most potent inhibitors. This encouraged us to optimize the modulation of the cyclization, and prepare a library of 15 β‐lactams with total regioselectivity. Moreover, we aimed to improve the bioavailability of these compounds through the introduction of diversity at different substitution positions. The activity of these compounds as apoptosis inhibitors in cellular extracts has been evaluated, showing an increase in their potency. Abstract : Family affairs : A sequence involving an Ugi multicomponent reaction followed by a completely regioselective cyclization under mild conditions made the preparation of a short library of β‐lactam derivatives possible. These β‐lactam derivatives show an improved profile as potential apoptosis inhibitors in terms of potency and water solubility.